An Ontology-based Representation Service of Context Information for the Internet of Things - Veiga, Ernesto Fonseca; Arruda, Mayke Ferreira; Batista Neto, José Augusto Batista; Bulcão-Neto, Renato de Freitas Bulcão (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2017: Proceedings of the 23rd Brazilian Symposium on Multimedia and the Web, 2017)
In the Internet of Things (IoT) paradigm, a context management system (CMS) should support the context life cycle including acquisition, modeling, reasoning and distribution of context information. The context modeling phase is responsible for the representation of context information in a format which should meet IoT requirements such as expressiveness, reuse, extension and interoperability. In this paper, we present the Hermes Widget IoT service, which represents context information using the semantics of IoT-oriented ontologies such as IoT-Lite and Semantic Sensor Network (SSN). As contribution, Hermes Widget IoT allows any context provider object (e.g. a sensor) to be located, used, and have its corresponding context information represented and made available for querying through the Internet.